Sintesis dan Karakterisasi SiO2@C dari Sekam Padi Sebagai Anoda Baterai Litium: - - Joko Suryadi; Eko Andrijanto; Mentik Hulupi; Shafira Salsabilla; Hani Hanifah (Fluida, 2025)
The rapid development of technology systems today has triggered a demand for battery development as energy storage. Utilizing the abundant biomass in Indonesia can meet commercial demands, one of which is rice husk. Rice husk is the protective layer that encases rice grains, containing holocellulose (55%), lignin (20%), SiO2 (20%), and minerals (5%), and has the potential to be used as a precursor for silica and carbon to create SiO2@C nanocomposites. In this study, SiO2@C composites were synthesized as lithium battery anode materials from rice husk using a calcination method and the addition of NaOH to form a porous morphology. The calcination process was carried out at 800℃ for 1 hour with a mass ratio of SP-C (Rice Husk Carbonization) and NaOH (1:1, 1:2, and 1:3). The synthesized SiO2@C composites exhibited a porous morphology within the mesopore size range of 13,94 nm at a 1:1 ratio and contained Si 2,42%, O 9,72%, and 87,86%. The mass ratio of NaOH addition can influence the surface area of the SiO2@C composites, with yields of 392,00 m2/g for 1:1 ratio, 1023,04 m2/g for the 1:2 ratio, and 1756,63 m2/g for the 1:3 ratio.